Reduced Expression of REG4 as a Sign of Altered Goblet Cell Function in Necrotizing Enterocolitis - Hoffsten, Alice; Markasz, Laszlo; Lilja, Helene Engstrand; Mobini-Far, Hamid; Sindelar, Richard (American Journal of Perinatology, 2024)
Objective Defective Goblet cells have been proposed to be involved in necrotizing enterocolitis (NEC). The aim was to study the expression of the Goblet cell marker REG4 and its potential involvement in NEC in preterm infants with and without NEC.Study Design Seventy histologically intact intestinal biopsies were studied: 43 were collected during surgery due to NEC (NEC group: 26.5 ± 3.0 weeks' gestational age [wGA]), and 27 from individuals who underwent surgery due to other conditions (Control group; 36.1 ± 4.5 wGA). The tissue samples were immunohistochemically stained for REG4. REG4 expression was quantified with a semiautomated digital image analysis and with clinical data compared between the groups.Results REG4 expression was lower in the NEC group than in the Control group (p = 0.035). Low REG4 expression correlated to the risk of NEC (p = 0.023). In a multivariable logistic regression analysis including GA and REG4 expression for NEC risk, only GA (p < 0.001) and not REG4 expression (p = 0.206) was associated with NEC risk.Conclusion This study concludes that Goblet cell dysfunction may be involved in NEC development, as low expression of the Goblet cell marker REG4 was related to an increased NEC risk in preterm infants. Maturity could however not be excluded as a potential confounder for REG4 expression.Key Points
Keywords: necrotizing enterocolitis; Goblet cell; REG4